Study the Role of India to Find Out a Suitable Solution of the Palestine Problem at Various Forums: India's Approach to the Palestinian Issue and the Role of Israel (Journal of Advances and Scholarly Researches in Allied Education, 2020)
The Indian mentality to the Palestinian issue, starting here onwards, was described by the acknowledgment of the truth of the state of Israel, a firm confidence in the need and plausibility of settling the Palestinian issue through exchanges and a profound worry for the destiny of the Palestinian outcasts who were removed from their homes because of the Arab-Jewish struggle over Palestine. When India perceived the presence of Israel as a set up reality, it certainly acknowledged the place that any solution set forward for taking care of the Palestinian outcast issue should address and deal with the real security interests of the Jewish state. To refer to only one case, in one of the preliminary gatherings in Colombo for the Afro-Asian Conference in Bandung in 1955, the Pakistani Prime Minister, Muhammad Ali, presented a draft resolution which, entomb alia, portrayed the formation of Israel as an infringement of international law.